STRATEGI E-COMMERCE MELALUI PENDEKATAN BUSINESS TO CONSUMER DALAM MANAJEMEN USAHA KECIL DAN MENENGAH DI INDONESIA - SUSANTO, RANDY (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Rapid technological advances make a difference to the behavior of transactions. Internet transaction is very visible and growing very rapidly, the increasing of Internet users give advantage of trading opportunities through the Internet. The using of e-commerce in particular through the business to consumer for SMEs should be implemented, even necessary strategies for business to consumer this can work well and can be implemented in the long term. Strategies that can be applied to SMEs in order to succeed is influenced by several factors, including the organization, management, technology, people, execution, trust. Implementation of business to consumer by SMEs is expected to increase competitiveness and market expansion. But the strategy of business to consumer also has advantages, disadvantages, and obstacles in the implementation for SMEs.